Isolations of the Spring Viremia of Carp Virus in the Upper Mississippi River (USA), Including a New Host, the Quillback. Issue 2 (8th May 2022) - Katona, Ryan; Standish, Isaac; McCann, Rebekah; Dziki, Sara; Bailey, Jennifer; Puzach, Corey; Warg, Janet; Leis, Eric; Phillips, Kenneth
Abstract: In July of 2018 and 2019, wild fish health surveys were conducted along the Wisconsin and Minnesota portions of the upper Mississippi River. Spring viremia of carp virus (SVCV) was isolated from Common Carp Cyprinus carpio as well as a newly identified host species, the Quillback Carpiodes cyprinus . Sanger sequencing of the gene encoding for the G protein revealed a high similarity of the Quillback isolate to various SVCV isolates identified from Common Carp that were collected during earlier wild fish health surveys and mortality events in the USA. Despite annual monitoring, this virus has been infrequently identified. The speculative role of native fish and invertebrates in allowing the virus to persist for long periods without detection is discussed.